STRATEGI KOMUNIKASI INTEGRASI INTERKONEKSI DALAM MENINGKATKAN KUALITAS SKRIPSI MAHASISWA (Studi Pada Dosen Program Studi Ilmu Komunikasi Fakultas Ilmu Sosial dan Humaniora UIN Sunan Kalijaga Yogyakarta) - Mokhamad Mahfud (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2015)
Thid research tend to describe the basic principals of the integration interconnection paradigm oblige any researcher to use four kinds of view in writing and reading integrated-interconnected researchs. Those are, first,triple hadarah (hadarah an-nas [religion], hadarah al-falsafah [philosphy], wa hadarah al-‘ilm [science]); second, “spider web” (religious knowledge, Islamic thought, and Islamic studies); third, “spheres and models” and forth, eight point views (summary, sense of academic crisis, importance of topic, prior research on topic, approach and methodology, limitation and key assumptions, contribution to knowledge, and logical squence).The communication strategy used by the lecturers of the Communication Science Department to advise the students in finishing their thesis is a way which is ethical and emancipathoric. The lecturers always advise the students in a humanist and elegant manner. The communication strategy is also educating, enlightening, empowering, and moving on.